Desenvolvimento de cartilha didática para o ensino de protozooses na educação básica - Aleixo, Eduardo da Costa Alves (2019)
Protozoans belong to the Protozoa Kingdom and some of them are parasites of different organisms, including humans, causing diseases generically called Protozoosis. Although the study of these diseases is provided in the curriculum of basic education, research indicates insufficient student performance on this topic. The low quality of the didactic material and excessively full of content classes are considered the main causes contributing to this situation. In the present work, five didactic booklets were produced about five main human Protozoosis: Malaria, leishmaniosis, toxoplasmosis, amoebiasis and Chagas disease, with special emphasis on source of infection, symptoms and prophylaxis of these diseases. The functionality of didactic booklets in the students‟ learning was tested in four high school classes of Rio de Janeiro state, through the construction of conceptual maps. Statistical analysis showed that the booklets about toxoplasmosis and malaria contributed significantly to the students' learning, increasing their performance in the construction of conceptual maps. The leishmaniosis booklet contributed to increase students‟ performance, but not in a statistically significant way. In the mirror group, which used the amoebiasis booklet, there was no significant difference between the conceptual maps made after the isolated use of the booklet and made after the standard expositive class, corroborating the efficient performance of the booklet in knowledge retention by students. The results of this work give us the perspective that other Biology content can be approached with the same methodology, providing one more aid tool to the teacher in the classroom.